ENVIRONMENTAL PARAMETERS FOR CAMPUS OUTDOOR SPACE: A MICROCLIMATE ANALYSIS OF THE EASTERN MEDITERRANEAN UNIVERSITY (EMU) CAMPUS - Fuladlu, Kamyar (College Publishing, 2021)
Open spaces-whether public, urban, or part of a campus-offer a variety of activities and opportunities to people. Therefore, open spaces should be considered a vital component of any built-up area and designed to meet the needs and address the comfort of potential users. Because of their presence in daily life and their preponderance of characteristics, open spaces have drawn the attention of many researchers, designers, and planners with varying perspectives. The current study takes a scientific approach to analyzing the environmental parameters of the Campus Outdoor Space (COS) in the case of the Eastern Mediterranean University (EMU). An extensive literature review supported the identification of seven important environmental parameters effective in the microscale analysis of a COS: geographical location, meteorological situation, urban form, surface materials, amount of vegetation and watershed, and anthropogenic pollution. Analysis of the environmental parameters called for a hybrid method that included a detailed field survey and the following set of simulations: sun-path, radiation, sky view factor, and turbulence analysis. The accuracy of the field survey directly contributed to the effectiveness of the simulations. Grasshopper (R) 3D software and Computational Fluid Dynamics were used to simulate the conditions of the EMU study area. The outcomes show that the spatial organization, building forms, and building orientation negatively affect the COS of EMU. In the Mediterranean climatic region of EMU, shade and flowing breezes greatly enhance comfort and usability of outdoor spaces from April to October. The massive form of buildings and minimal planning for effective building orientation to the sun increased heat storage capacity and neglected prevailing winds, resulting in flow separation and formation of eddies on the leeward side of buildings. These negatively influenced the microclimate, and thereby user comfort, at the core of the EMU's main COS.
Keywords: Campus Outdoor Space; Computational Fluid Dynamics; Grasshopper (R) 3D; Microclimate